PARTISIPASI PETANI DALAM PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) DI KECAMATAN ADILUWIH KABUPATEN PRINGSEWU - Rika ES Sitompul; Kordiyana K Rangga; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The objectives of this research are to know the participation of farmers in PUAP program, factors related to farmers’ participation in PUAP program, and farmers’ income. This research was conducted in Bandung Baru Village of Adiluwih District, Pringsewu Regency. The sampling used was proportional random sampling with total of 81 farmers. The research was conducted in October - December 2016. The research method is a survey. The relationship between the variables was tested using Rank Spearman correlation test. The results showed that farmers' participation in the PUAP program was quite active, factors related to farmers’ participation were age, education level, length of farming experience, and cultivated land area.  Average household income of farmers in Bandung Baru Village Adiluwih District Pringsewu Regency each year is Rp67.633.851. Key words: income, participation, PUAP program